Effect of body mass index on the survival of patients with early-stage small cell lung cancer after surgery - Kolesnik, A. P. (Zaporozhye Medical Journal, 2013)
Lung cancer is an important medico-social problem. It is connected with high level of incidence and mortality of lung cancer. Nowadays we know that obesity has significant influence on cancer development, including lung cancer. Multivariate analysis confirmed that histological type of tumour, kind of operation and body mass index (BMI) influence on prognosis in patients with early stages of mall cell lung cancer. So, now we can use BMI along with other significant prognostic criteria for detection of unfavorable prognostic group of patients.